Boosting students’ self-directed english learning through social media engagement - Ade Ismail Ramadhan Hamid; Khusnul Khatimah (Institute of Computer Science (IOCS), 2026)
This study investigates how social media platforms can be leveraged to enhance self-directed English language learning among Muhammadiyah students. Utilizing a quantitative approach, data were collected from 72 students via a structured questionnaire measuring both social media use for English learning and self-directed learning (SDL) behaviors. Descriptive statistics revealed high engagement with social media for English learning (mean = 4.07) and robust self-directed learning tendencies (mean = 3.77), with no significant gender differences. Correlation analysis demonstrated a strong, statistically significant positive relationship between social media use and SDL (Pearson r = 0.793, p < 0.001). These findings suggest that social media is not only widely used and effective for English language learning but also a powerful enabler of self-directed learning in this context. The study highlights the potential of social media to bridge gaps in English education in geographically isolated regions and provides actionable insights for educators and policymakers seeking to foster autonomous, motivated language learners in Muhammadiyah institutions